The Development of Massive Open Online Course (MOOC) Innovation on “Mental Health Enhancement of the Elder with Integrative Techniques for Elderly Caregivers” - Wongtim, Sukaroon (Journal of The Royal Thai Army Nurses, 2023)
The objectives of this research were 1) to develop innovative Thai massive open online course for elderly caregivers on the program promoting mental health of older people with integrated techniques, and 2) to study effectiveness of the lessons. The sample was 400 learners who studied this online lesson during 2-12 September 2022. They were examined before, during, and after the course to measure learning outcomes and they also answered the opinion questionnaires. The instruments were 1) Thai massive open online course for elderly caregivers on the program promoting mental health of older people with integrated techniques 2) questionnaire measuring learning results, with difficulty 0.50 and discrimination power 0.31-0.36 and 3) online questionnaire about opinion of this course. Statistics used were percentage, mean, standard deviation, t-test, and factor analysis. The results of the research were as follows: 1) The online lessons were an innovation for lifelong learning of elderly caregivers. The highlight of the lesson made the learners understand psychology of the elderly and they could choose a variety of care techniques which was appropriate for each elderly person through clips of lectures and demonstrations of various techniques to enable practice and return-demonstration with confidence. 2) The score after learning was higher than before learning with statistical significance at .05 level, and having the total average score of 92%. The learners’ opinions showed that this course was good quality, update, and effectiveness for take care their elderly.